Experimental research into the ignition and combustion characteristics of slurry fuels based on dry and wet coal processing waste; Journal of the Energy Institute; Vol. 97 - Kuznetsov G. V. Geny Vladimirovich; Nyashina G. S. Galina Sergeevna; Strizhak P. A. Pavel Alexandrovich; Valiullin T. R. Timur Radisovich (2021, 2021)
Title screen